Pencegahan Stunting Melalui Edukasi (Sosialisasi Stunting dan MPASI, Senam Hamil, Pemberian Tablet Tambah Darah) Bagi Masyarakat - Agustina, Lina; Agustina, Putri; Astuti, Rina; Santhyami, Santhyami; Aryani, Ima; Roziaty, Efri (Dharma: Jurnal Pengabdian Masyarakat, 2025)
This community service project aims to educate the community about stunting. The employed approaches include observation, socialisation (specifically stunting socialisation, pregnant exercises, and the distribution of iron supplements), and interviews. The event took place at the village hall in Sukoharjo district on August 13, 2024, with 19 people in attendance. The activity's results indicated that the stunting education was conducted effectively, with participants demonstrating enthusiasm. They reported an increased awareness of the dangers of stunting, prompting them to enhance nutritional intake during pregnancy and for toddlers, thereby promoting optimal growth and development in children. This activity has led to an enhanced comprehension among participants regarding stunting, complementary feeding (MPASI), the risks of anaemia in pregnant women, and prenatal exercises that better equip them for childbirth.